PENGARUH PELAKSANAAN PROGRAM PELATIHAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DI HOTEL FAIRMONT SANUR BEACH BALI BAGIAN ROOM DIVISION - Yulius, Kevin Gustian; Hezkiel, Jane; Hans, Stephany; Vivian, Vivian (Jurnal Ilmiah Pariwisata, 2019)
The hospitality industry is the part of the tourism industry which is the 4th highest devisa contributor of Indonesia. Bali nicknamed as the Island of Gods is one of the most favorite destination with stable and increasing number of visitors each year. One of the most important part of a hotel is its’ human resources and as the heart of the hotel, the performance of the room division staffs can be used as a benchmark of the hotel’s success. Performance improvement can be done with training and development. This research intended to measure the impact of training and development as indepent variables toward staffs’ performance as the dependent variable in room division of Hotel Fairmont Sanur Beach Bali. This research used descriptive quantitative method and correlational analysis. The sample in this research was 66 staffs from both the Front Office and Housekeeping determined with Slovin formula. Using the measurement of determinant coefficient, it was discovered that training and development influence the performance by 53,9% while the rest was influenced by other variables outside this research. From the result of this research, it may be concluded that training and development influenced the room division staffs performance positively, whether partially and simultaneously.